Designing a mobile sales application at Setra farma pharmacy in the era of the covid-19 using the goal-directed desing method - Annisa Anggraeny; Mochzen Gito Resmi; Syariful Alam (Jurnal Mantik, 2022)
Setra Farma Pharmacy is a company that handles product and servicesn by providing services in the form of pharmaceutical servies. Setra Farma pharmacies like the accumulation of queues of buyers and the absence of queue numbers especially in Covid-19 is very prone to infection. With this, Apotek Setra Farma wants to develop a mobile-based sales application to assist patients in finding and ordering drugs. This study uses the Goal-Directed Design method with prorotype testing using the single ease question method. When testing the user will be given a task that is rated on a 1-7 point linkert scale. The result of this research is the user interface application mobile that can be used at the Setra Farma Pharmacy. The final results obtained after testing the prototype with 5 users showed a score of 6.6 on the linkert scale of 1-7 points,which means the application is easy for users to use.